2018
DOI: 10.7287/peerj.preprints.26637
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The neuronal migration hypothesis of dyslexia: a critical evaluation thirty years on

Abstract: 1The capacity for language is one of the key features underlying the complexity of human 2 cognition and its evolution. However, little is known about the neurobiological mechanisms that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Our study supports the emerging role for KIAA0319 in sensory organs adding to the debate around the different theories aimed at explaining the pathophysiology of developmental dyslexia. In particular, this study will contribute to the ongoing discussion around the role of neuronal migration in dyslexia (39), first proposed in the eighties and corroborated by the initial characterization of susceptibility genes, including KIAA0319.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our study supports the emerging role for KIAA0319 in sensory organs adding to the debate around the different theories aimed at explaining the pathophysiology of developmental dyslexia. In particular, this study will contribute to the ongoing discussion around the role of neuronal migration in dyslexia (39), first proposed in the eighties and corroborated by the initial characterization of susceptibility genes, including KIAA0319.…”
Section: Discussionsupporting
confidence: 52%
“…The function of the KIAA0319 protein has been studied in human cell lines and in rodent models, however it has not been fully elucidated yet. The first functional characterization was conducted in rats and suggested a role in neuronal migration (11) while more recent studies in mouse indicated an involvement in biological processes beyond brain development (25,31,39).…”
Section: Kiaa0319-like Reported In Human Tissues (Supplementarymentioning
confidence: 99%
“…Such anomalies are likely to be the result of neuronal migration defects. However, knockout mouse models for DYX1C1, DCDC2 and KIAA0319 did not exhibit cortical alterations [5], although heterotopias were observed in rats subjected to in utero knockdown of Dyx1c1 [6].…”
Section: Introductionmentioning
confidence: 92%
“…KIAA0319 encodes a transmembrane protein with five PKD domains [14,15] ( Figure 1A). Such structures have been previously found in cell surface proteins and are known to be involved in cell-cell and cell-matrix interactions [16] but the cellular function of KIAA0319 remains largely uncharacterised [5]. KIAA0319 has also been suggested to play a role in signalling pathways [17] and in axon growth inhibition [18].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation